2010
DOI: 10.1007/s10661-010-1799-3
|View full text |Cite
|
Sign up to set email alerts
|

Personal and indoor exposure to PM2.5 and polycyclic aromatic hydrocarbons in the southern highlands of Tanzania: a pilot-scale study

Abstract: Personal and indoor exposure to PM(2.5) and polycyclic aromatic hydrocarbons (PAHs) were measured in households in the Njombe district of Tanzania. Cooking is conducted indoors in this region due to its high elevation, cool climate, and heavy seasonal rainfall. Kitchens are often poorly ventilated, resulting in high exposures to combustion-related pollutants. Sampling sites were selected to represent typical cooking practices across regional socio-economic divisions. These include the use of open wood fires, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 43 publications
8
45
2
Order By: Relevance
“…The concentrations of PAH was highest in the kitchen than in outdoor and living room, respectively, and this observation could not be considered weird taking into account the cooking activities (source strength) and the type of biomass fuels that are used in kitchens where no proper ventilation system exists. Individual PAH concentration in kitchens with wood stoves are significantly elevated than those using charcoal by over an order of magnitude, suggesting further that wood stoves or wood burning devices are big emitter of PAHs, firmly consistent with previous studies [22,27,32]. Studies have shown that PAHs are highest in a similar environment where an indoor source (cooking or space heating or environmental tobacco smoke) dominate [33,34].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The concentrations of PAH was highest in the kitchen than in outdoor and living room, respectively, and this observation could not be considered weird taking into account the cooking activities (source strength) and the type of biomass fuels that are used in kitchens where no proper ventilation system exists. Individual PAH concentration in kitchens with wood stoves are significantly elevated than those using charcoal by over an order of magnitude, suggesting further that wood stoves or wood burning devices are big emitter of PAHs, firmly consistent with previous studies [22,27,32]. Studies have shown that PAHs are highest in a similar environment where an indoor source (cooking or space heating or environmental tobacco smoke) dominate [33,34].…”
Section: Discussionsupporting
confidence: 87%
“…But the toxicity estimate measured by the BaPeq concentrations in this study in all of the three locations is not negligible since the threshold of 1 ng/ m 3 suggested by WHO for inhaled air was exceeded. The mean BaPeq concentration in the current study is lower than two previous studies conducted during cooking in kitchens with wood and charcoal stoves in Sierra Leone; 616 ng/m 3 and 58 ng/m 3 [27]; and in Tanzania; 391 ng/ m 3 and 92 ng/m 3 [32] but higher than the levels reported for children's exposure in outdoor air in New York 0.45 ng/m 3 [43].…”
Section: Locationcontrasting
confidence: 88%
See 1 more Smart Citation
“…A study from the highlands of Tanzania examined PM 2.5 and PAH concentrations in households burning different fuels for cooking (Titcombe and Simcik, 2011). The fuels used were liquefied petroleum gas (LPG), a kerosene/charcoal mix, charcoal, and wood (open burning).…”
Section: Characterization Of Amounts Selected Sources and Health Efmentioning
confidence: 99%
“…Therefore, fewer PAH emissions are expected when grilling foods with liquefied petroleum gas as fuel compared with charcoal as fuel. Furthermore, liquefied petroleum gas combustion during cooking causes lower concentrations of ambient PAHs than does charcoal consumption (Titcombe and Simcik, 2011). However, the PM 10 -bound PAH concentrations in the barbecue night markets in Hefei City were 1-2 orders of magnitude higher than those detected in urban areas (Mantis et al, 2005;Hong et al, 2007;Vu et al, 2011;Limu et al, 2013;Wu et al, 2014a), indicating that staff and consumers in barbecue night markets are significantly exposed to carcinogenic PAHs.…”
Section: Pm 10 and Pah Concentrationsmentioning
confidence: 94%